Castles in the Clouds: LiDAR for Historical Study and Terrain Analysis - Guth, Peter L (Scientia Militaria - South African Journal of Military Studies, 2018)
Examples of castles and fortresses seen in publicly available LiDAR data by the national mapping agencies in Finland, the Netherlands, Norway, Slovenia, the United Kingdom, and United States demonstrate the value of LiDAR data for understanding military history. The data sets, which include derived grids and the original point clouds with densities from 2–24 points/m², always identify the ground points, generally include LiDAR return intensity values, and sometimes include point classifications that discriminate vegetation and buildings. Grids with 0,5- or one-metre resolution could be created from the highest density point clouds in this study, while grids with one- or two-metre resolution can be created from the lowest density clouds. The digital surface model, which includes everything seen by the sensor, notably ground, buildings, and vegetation, can be created with higher resolution than the bare earth grids. The surface model provides the best visual representation of the castle and its surroundings. Viewed in interactive 3D, the data allows familiarisation with the landscape. Optimal displays depend on the desired scale and the terrain characteristics, but hillshade or shaded reflectance maps, reverse greyscale slope maps, and openness maps all work effectively. Further analysis may include functions such as viewsheds, which enhance the understanding of key terrain.